The Internet and political (in)equality in the Arab world: A multi-country study of the relationship between Internet news use, press freedom, and protest participation. (May 2019) - Ahmed, Saifuddin; Cho, Jaeho
This study investigates the role of the Internet in protest participation in the Arab world. More specifically, we aim to address three important questions: (1) Does Internet news use increase the chances of protest participation? (2) Does Internet news use amplify or reduce participation gaps that exist among individuals at various socioeconomic strata? (3) How does a country's press freedom act as a contextual factor to shape the role of the Internet in affecting protest participation gaps? The results based on an analysis of the third wave of Arab Democracy Barometer survey suggest that Internet news use for political purposes increases the likelihood of protest participation in the Arab world while it also deepens socioeconomic stratification in participation. Furthermore, national press freedom shapes the intervening role of the Internet. We discuss the theoretical implications of these findings for political inequality literature and the practical consequences for the Arab world.